History and implications of the Nares Strait conflict - Kerr, J. William (Meddelelser om Grønland. Geoscience, 1982)
The question "Did Greenland drift along Nares Strait?" has been debated for more than 70 years. There have been five periods, each represented by a consensus on one or the other extreme, or by a conflict. At times opinions on the Strait have changed rapidly when a new global theory came in or went out. There is a possibility that at these times opinion on the Strait has been determined more by theory than by evidence. At present there is a conflict. One group of earth scientists have worked on the shores of the Strait and have correlated stratigraphic and structural features across it. They conclude that a slight movement of some kilometres, but not exceeding 25 km, may have occurred. Another group have worked in the oceanic basins surrounding Greenland and their conclusion is that there has been 220 km or more of sinistral movement along the Strait. The solution to the Nares Strait conflict appears to be clear-cut. We must determine whether displacement was a) less than 25 km orb) more than 220 km. There have been no serious suggestions about sinistral motion between these two extremes. The origin of Nares Strait has enormous implications for tectonics. The Strait is an important element in tectonics of the northern hemisphere, and it is a key to the pre-drift position of Greenland. It is thereby an important feature in the reconstruction of the North Atlantic Ocean as well as the Arctic Ocean. If there has been hundreds of kilometres of sinistral displacement of Greenland along the Strait, then much support is given to the conventional plate tectonic theory which is widely accepted today. If displacement was minor, or non-existent, then plate tectonic theory is faced with a major problem: what are the origins of Baffin Bay and Labrador Sea?